Information Dissemination on Regulation of Supreme Court Number 1 Year 2016 Regarding Mediation in the Village of Maleber Bandung - Moody R. Syailendra; Indah Aprilia; Anggraeni Sari Gunawan; Shrishti Shrishti (Journal of Innovation and Community Engagement, 2022)
As mentioned by article 1 point 1 in Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016, mediation is an alternative resort to solve disputes through negotiation used to reach a consensus in the presence of a mediator. Mediation as an alternative dispute resolution reflects the Fourth Precept of Pancasila as the nation's character which implies resolving disputes through deliberation. Prioritizing communication is a form of deliberation carried out with the purpose of re-agreements, where there will be a possibility to improve the relationship between the parties. Resolving conflicts through mediation is an attempt to end complicated issues through a process that is time-saving and relatively cheap in providing win-win solutions. In Indonesia, the existence of mediation is based on the Regulation of the Supreme Court of the Republic of Indonesia No. 1 of 2016. Mediation has also been set as a mandatory process in the path of resolving disputes in the civil court. The method of information dissemination is carried out to create awareness regarding the new law enforced, which includes lectures and interaction. The research team in collaboration with the Maleber Village held an information dissemination activity based on the Supreme Court Regulation Number 1 of 2016 concerning Mediation. This activity would be very useful for all the parties facing conflicts as well as advisors or for third parties (mediators), such as the village apparatus, families, traditional leaders, community leaders, and other parties who are becoming completely aware of the negotiation and mediation.